The city as the habitar's space and the idea of the cities factory (Research, Society and Development, 2020)
Citizenship of dwelling is a challenge of the state, governments and society itself. Therefore, urban public policies, specifically housing policies, must be oriented and acted so that they become viable or concrete. Thus, the question of study to be discussed has the city as a place of manifestation of citizenship and the exercise of social rights, by guaranteeing access to housing, transformed into the place where citizens live (live, live and manifest themselves). In this sense, in what aspects can this perspective of guaranteeing access to housing be guaranteed or improved? The objective was to discuss about the construction of the city factory, elements and guidelines for the guarantee of citizenship of housing, from its perspective of housing space in the municipal sphere (cities or neighborhoods). This is a qualitative exploratory research on secondary data to explore and build the construct of city factories. Thus, the construction of city factories, following this study, involves a public policy (project and program) for the construction of spaces (cities or neighborhoods) that will be the places for the exercise of citizenship of dwelling, contemplating in its orientation the concepts, principles and elements of smart and self-sustaining cities or spaces (smart cities) and their execution elements, so that citizenship of dwelling, when built, has the participation and legitimacy of social actors, who will enjoy this space.